2021
DOI: 10.3389/fimmu.2021.728291
|View full text |Cite
|
Sign up to set email alerts
|

Role of Decidual Natural Killer Cells in Human Pregnancy and Related Pregnancy Complications

Abstract: Pregnancy is a unique type of immunological process. Healthy pregnancy is associated with a series of inflammatory events: implantation (inflammation), gestation (anti-inflammation), and parturition (inflammation). As the most abundant leukocytes during pregnancy, natural killer (NK) cells are recruited and activated by ovarian hormones and have pivotal roles throughout pregnancy. During the first trimester, NK cells represent up to 50–70% of decidua lymphocytes. Differently from peripheral-blood NK cells, dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 153 publications
2
80
0
1
Order By: Relevance
“…It was shown that the number of cytotoxic uNK cell-surface receptors on uNK cells and increased number of immature uNK cells was upregulated in the endometrium of infertile females with endometriosis, compared to fertile females. Moreover, NKp44 expression on uNK cells was significantly increased in RIF patients and indicated that NK cells’ cytotoxicity may cause the recurrent implantation failure [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the number of cytotoxic uNK cell-surface receptors on uNK cells and increased number of immature uNK cells was upregulated in the endometrium of infertile females with endometriosis, compared to fertile females. Moreover, NKp44 expression on uNK cells was significantly increased in RIF patients and indicated that NK cells’ cytotoxicity may cause the recurrent implantation failure [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, dNK cells are crucial to successful placentation through the orchestration of trophoblast invasion and endometrial vasculature remodelling. Although not entirely understood, dNK cells are thought to be important for the induction of immune tolerance and maintaining a tolerogenic environment at the maternal decidua ( 47 ). Given their specialised nature, it is no surprise that dNK cells have a unique functional phenotype.…”
Section: Phenotype and Function Of Tissue-resident Nk Cellsmentioning
confidence: 99%
“…Most notably, dNK cells produce an array of pro-angiogenic factors such as vascular endothelial growth factor (VEGF), placental growth factor (PIGF), and angiopoietin-2 (Ang-2). In addition, dNK cells produce various immunoregulatory cytokines such as, transforming growth factor beta (TGFβ), GM-CSF, IL-8, and IL-10 ( 47 ), and are poorly cytolytic ( 46 ). Considering this, tumor-infiltrating NK cells displaying a dNK-like phenotype are unlikely to result in beneficial disease outcomes ( Figure 2 ).…”
Section: Phenotype and Function Of Tissue-resident Nk Cellsmentioning
confidence: 99%
“…In general, there is no uniform evidence that the above-mentioned immunotherapeutic approaches benefit clinical outcomes in patients; and there is no consensus on the role of uNK cells in RM or RIF ( 180 ). However, recent studies have shown that uNK cells have special physiological functions in reproduction, especially in the establishment and maintenance of pregnancy ( 182 , 183 ), and corticosteroids/intralipid therapy that suppress NK cells activity may exacerbate pregnancy failure ( 184 , 185 ). Additionally, the state of the endometrium or the risk of pregnancy disease may be predicted by the examination of uNK cells in menstrual blood ( 25 ).…”
Section: Potential Of Unk Cells In Treating Reproductive Diseasesmentioning
confidence: 99%